Pedagogical guidelines for strengthening teacher performance evaluation in the district of Turbo, Colombia - Caicedo, Jarrison (2022)
Throughout history it has been proven that one of the ways to improve the quality of education in countries is through the improvement of teaching career systems, especially in the component where the performance evaluation process is applied, which in turn contributes to the professional development of teachers. The objective of this article is to make a theoretical-conceptual reflection on the performance evaluation applied to teachers and the influence it has on their professional growth, with the intention of making a partial or definitive synopsis of the discourse from the author's point of view, obviously starting from the point of view of the postulates of several authors and the review of the existing literature on the variables performance evaluation, teacher performance, pedagogical guidelines and professional development. The information was collected through a documentary search in publications of scientific journals and digital repositories; search criteria were established for tracking the information such as locating the publications on the variables, and delimiting them according to the topic of each one. It is reflexively concluded that several authors propose the need to implement efficient teaching career systems for the strengthening of performance evaluation through the design of pedagogical guidelines with which the evaluation can be optimally applied and thus contribute to the professional development of teachers